2019
DOI: 10.1021/acs.nanolett.9b01844
|View full text |Cite
|
Sign up to set email alerts
|

Multiantigenic Nanotoxoids for Antivirulence Vaccination against Antibiotic-Resistant Gram-Negative Bacteria

Abstract: Infections caused by multidrug-resistant gram-negative bacteria have emerged as a major threat to public health worldwide. The high mortality and prevalence, along with the slow pace of new antibiotic discovery, highlight the necessity for new disease management paradigms. Here, we report on the development of a multiantigenic nanotoxoid vaccine based on macrophage membrane-coated nanoparticles for eliciting potent immunity against pathogenic Pseudomonas aeruginosa. The design of this biomimetic nanovaccine le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 64 publications
2
84
0
1
Order By: Relevance
“…Following the synthesis, the measurement of OM‐NPs with dynamic light scattering showed a hydrodynamic diameter of 105.7±3.1 nm (Figure B). The diameter increased by approximately 18 nm compared to that of the bare PLGA cores, consistent with the addition of a thin lipid bilayer onto the nanoparticle surface . Meanwhile, the surface zeta potential of the nanoparticles changed from −40.6±5.3 mV of PLGA cores to −28.8±1.9 mV of OM‐NPs.…”
Section: Figuresupporting
confidence: 87%
“…Following the synthesis, the measurement of OM‐NPs with dynamic light scattering showed a hydrodynamic diameter of 105.7±3.1 nm (Figure B). The diameter increased by approximately 18 nm compared to that of the bare PLGA cores, consistent with the addition of a thin lipid bilayer onto the nanoparticle surface . Meanwhile, the surface zeta potential of the nanoparticles changed from −40.6±5.3 mV of PLGA cores to −28.8±1.9 mV of OM‐NPs.…”
Section: Figuresupporting
confidence: 87%
“…As therapeutic nanoparticles are gaining traction for potential HIV treatment and prevention, cell membrane-coated nanoparticles, made by wrapping plasma membranes of natural cells onto synthetic nanoparticle cores, are emerging as a biomimetic platform to treat various diseases ( 25 32 ). This unique biomimicry led us to assess this technology as a potential HIV treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Wei et al [44] reported a macrophage-membrane-coated nanotoxoid against pathogenic Pseudomonas aeruginosa . It has already been reported previously that alveolar macrophages have cationic proteins that can bind to the outer membrane of the bacteria Pseudomonas aeruginosa, and its flagella also get involved in phagocytosis.…”
Section: Components Of Biomimetic Immunomodulatory Nanovaccinesmentioning
confidence: 99%
“…Hu et al [42] reported the first membrane-coated NPs where red blood cell (RBC) membranes were coated over a polymeric NP through extrusion [42]. Many types of membranes from different sources, such as RBCs [41,42,43], leukocytes [44,45,46], cytotoxic T-cells [47], NK cells [48], platelets [49], macrophages [44,50], and cancer cells [51,52], have been used in the preparation of membrane-coated NPs. Another type of biomimetic nanovaccine can be self-assembling proteins, which are known to have high symmetry and stability, and can be structurally organized into particles of sizes (10–150) nm [53,54].…”
Section: Introductionmentioning
confidence: 99%